2016
DOI: 10.1002/dmrr.2743
|View full text |Cite
|
Sign up to set email alerts
|

Where frailty meets diabetes

Abstract: Diabetes is a chronic illness that has an effect on multiple organ systems. Frailty is a state of increased vulnerability to stressors and a limited capacity to maintain homeostasis. It is a multidimensional concept and a dynamic condition that can improve or worsen over time. Frailty is either physical or psychological or a combination of these two components. Sarcopenia, which is the age-related loss of skeletal muscle mass and strength, is the main attributor to the physical form of frailty. Although the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 93 publications
3
100
0
5
Order By: Relevance
“…Although investigations into T2DM pathophysiology commonly focus on insulin resistance, and impaired insulin secretion, recent data suggest a broader range of causes. Since T2DM has begun to be considered as a model of “accelerated aging” [39, 40], LTL shortening has been hypothesized to be indicative of senescent cell accumulation and of an increased burden of systemic inflammation [41]. Although inflammation has been suggested to have a key role in T2DM development and progression, its molecular bases are still being investigated [4244].…”
Section: Discussionmentioning
confidence: 99%
“…Although investigations into T2DM pathophysiology commonly focus on insulin resistance, and impaired insulin secretion, recent data suggest a broader range of causes. Since T2DM has begun to be considered as a model of “accelerated aging” [39, 40], LTL shortening has been hypothesized to be indicative of senescent cell accumulation and of an increased burden of systemic inflammation [41]. Although inflammation has been suggested to have a key role in T2DM development and progression, its molecular bases are still being investigated [4244].…”
Section: Discussionmentioning
confidence: 99%
“…When screened for in a population of people with DM, the prevalence of frailty also varied and was reported to be between 5-48% [31]. Several studies have shown that older DM patients were more likely to be frail than their non-DM counterparts [19][20][21][32][33][34][35].…”
Section: Prevalence Of Frailtymentioning
confidence: 99%
“…Sarcopenia, particularly for type II fibers is a hallmark of inactivity and aging (14, 44, 58). Indeed the development of comorbidities such as kidney disease, atherosclerosis, and diabetes, which may contribute to accelerated sarcopenia, are not uncommon as the population ages (14, 44).…”
Section: Discussionmentioning
confidence: 99%